Development of unconventional ways to improve performance of the axial piston hydromashines taking into account repair abilities - Довбенко, Марк Николаевич; Евдокимов, Вадим Дмитриевич (Eastern-European Journal of Enterprise Technologies, 2014)
As a result of studies, operating conditions of friction pairs of axial piston hydromachine parts were examined and real ways to use a number of tribological techniques to improve their performance were shown. It was found that the most simple methods that increase the performance of the friction units of axial-piston hydromachines, are using surfactants in hydraulic oil, creating conditions for the manifestation of the selective transfer with forming a thin copper film on the steel parts and using mobile insertions of active materials. A summary table with the main advantages of the considered unconventional methods that improve the running-in quality of axial-piston hydromachine parts and their friction units, which is of practical value for the operators and industrialists during repair works was given. The main advantages and disadvantages of unconventional methods, applicable for improving axial piston hydromachine durability were shown. So using surface active liquid additives increases wear resistance by 3 times, load-bearing capacity by about 2 times with the possibility to replace bronze with steel. Creating conditions for selective transfer provides smaller parameters that increase hydromachine performance and requires another liquid lubricating medium such as glycerin. A more efficient method is using special active solid lubricants, which allows not only to abandon hydrocylinder bronze blocks, replacing them with steel, but also enhance the durability up to 5 times, and fluid working pressure up to 400 atmospheres. This compensates for the costs, associated with manufacturing narrow pockets for a solid lubricant.